1-Deoxynojirimycin (DNJ) Ameliorates Indomethacin-Induced Gastric Ulcer in Mice by Affecting NF-kappaB Signaling Pathway - Piao, Xuehua; Li, Shuangdi; Sui, Xiaodan; Guo, Lianyi; Liu, Xingmei; Li, Hongmei; Gao, Leming; Cai, Shusheng; Li, Yanrong; Wang, Tingting; Liu, Baohai (Frontiers in Pharmacology, 2018)
Gastric ulcer (GU) is a main threat to public health. 1-deoxynojirimycin (DNJ) has antioxidant and anti-inflammatory properties and may prevent GU but related mechanism remains unclear. DNJ was extracted from the supernatants of Bacillus subtilis by using ethanol and purified by using CM-Sepharose chromatography. A GU mouse model was induced by indomethacin. The functional role of DNJ in GU mice was explored by measuring the main molecules in the NF-Kappa B pathway. After the model establishment, forty GU mice were evenly assigned into five categories: IG (received vehicle control), LG (10 μg DNJ daily), MG (20 μg DNJ daily), HG (40 μg DNJ daily) and RG (0.5 mg ranitidine daily). Meanwhile, 8 healthy mice were assigned as a control group (CG). After one-month therapy, weight and gastric volume were investigated. The levels of serum inflammatory cytokines (IL-6 and TNF-α), antioxidant indices (superoxide dismutase (SOD), catalase (CAT) and reduced glutathione (GSH)), and oxidant biomarker malondialdehyde (MDA) were examined via ELISA. Meanwhile, inflammatory cytokine (IL-6 and TNF-α) levels, and key molecules (NF-κB p65, cyclooxygenase 1 (COX-1) and COX2) involved in NF-κB pathway, were analyzed by using Western Blot. COX-1 and COX-2 levels were further measured by immunohistochemistry. The effects of DNJ on gastric functions were explored by measuring the changes of Motilin (MOT), Substance P (SP), Somatostatin (SS) and Vasoactive intestinal peptide (VIP) in GU mouse models with ELISA Kits. The results indicated that DNJ prevented indomethacin-caused increase of gastric volume. DNJ improved histopathology of GU mice when compared with the mice from IG group (P <0.05). DNJ consumption decreased the levels of IL-6 and TNF-α (P < 0.05). DNJ increased antioxidant indices of GU mice by improving the activities of SOD, CAT and reduced GSH, and reduced MDA levels (P<0.05). DNJ increased the levels of prostaglandin E2, COX-1, COX2, and reduced the levels of and NF-κB p65 (P<0.05). DNJ showed protection for gastric functions of GU mice by reducing the levels of MOT and SP, and increasing the levels of SS and VIP. DNJ treatment inactivates NF-κB signaling pathway, and increases anti-ulceration ability of the models.